Problemas familiares y autoestima en el adulto mayor de 78 años en la Parroquia Ricaurte del Cantón Urdaneta de la Provincia de Los Ríos - Quinatoa Chimbo, Lita Isabel (2023)
The family plays a very important role in socio-affective relationships, since it is the most suitable for facilitating feelings of security, usefulness, self-esteem, trust and social support. In the elderly, it would be much easier and more bearable if family relationships are softened in a considerate, healthy and adequate environment for the elderly where family problems that may affect the elderly do not arise. The objective of this research is to determine family problems and self-esteem in the elderly. Through a qualitative study from a qualitative research approach based on interviews and tests applied to the elderly. The results obtained lead to a deep reflection on how feelings within the home have serious consequences for the health and low self-esteem of older adults. It is necessary to foster within the family relationships the acceptance of the older adult's self, to give him more affection within the home; to provide him with security when he believes that because of his age he is useless or a hindrance, when he does not accept the changes in his body and gets depressed, when he is negative, pessimistic and finds it difficult to give and receive affection.